Economic Reforms Create Opportunities in Africa - Okoroafo, Sam C (Management decision, 1992)
Highlights economic reform policies recently instituted in a number of sub-Sahara African countries. The reforms have drastically transformed these economies: import restrictions have been removed; currencies′ values are now determined by supply and demand; state-owned firms are on the auction block. For international firms, there has never been a better time to invest. However, the old rules for analysing foreign markets still apply. Caution is still the watchword.